In the Footsteps of Gilgamesh: - In Search of the "Prickly Rose" - During Caspers, E. C. L.
develops the hypothesis that the mythical "plant" of rejuvenation, the ?iš-nim-?ír = amurdinnu, can be a coral tree of the order Antipatharia or Gorgonacea